2015
DOI: 10.1590/0034-7167.2015680607i
|View full text |Cite
|
Sign up to set email alerts
|

Replicação de programa de capacitação em comunicação não verbal em gerontologia

Abstract: it was concluded that the replication of this program was relevant and current for the hospital context, remaining effi cient for healthcare professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
0
5
0
3
Order By: Relevance
“…Hemodialysis treatment is continuous and becomes a routine, and nursing care involves technical actions and reaches the understanding of the unspoken, of what cannot be said in words, but through gestures. (3,13,14) In this scenario, the intimate distance predominates during patients' arrival, at the times of user embracement, in patients' accommodation to the machine, in the arteriovenous fistula puncture, removal of venous accesses and while performing dressings. Care provision requires a maximum approximation between nursing professionals and patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hemodialysis treatment is continuous and becomes a routine, and nursing care involves technical actions and reaches the understanding of the unspoken, of what cannot be said in words, but through gestures. (3,13,14) In this scenario, the intimate distance predominates during patients' arrival, at the times of user embracement, in patients' accommodation to the machine, in the arteriovenous fistula puncture, removal of venous accesses and while performing dressings. Care provision requires a maximum approximation between nursing professionals and patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is close bonding because relationships occur all the time, on alternate days, month after month, year after year, determining an intense approximation because of the length of stay and continuous treatment. (13)(14)(15) Considering the nonverbal communication of the nurse and the patient each day, it stands out that the social distance established during interactions depends on the relationship of individuals involved, the present feeling, and the type of care needed at that time. In the intradialytic period, there was predominance of social proxemic communication that changed to intimate distance only when the patient presented clinical involution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the correct identification of non-verbal signs requires training and disposition, so that it is possible to distinguish the nuances related to the other, allowing for a reliable understanding of the message conveyed. 7 The analysis of the correlation between the indicators of pleasure and suffering and interpersonal communication showed significant values, and it was observed that the experiences of pleasure generate a positive influence on communication among the Nursing team members. On the other hand, the greater the suffering at work, the lower the levels of communication among professionals.…”
Section: /13mentioning
confidence: 98%
“…6 Verbal communication is associated with the externalization of words, through the use of writing or speech as a mechanism to convey the intended message. 7 Non-verbal communication comprises all information that can be obtained through gestures, postures, facial and body expressions, silence, mannerisms, volume and rhythm of the voice, level of physical energy, body orientations, presence and characteristics of touch, interpersonal distance, nods, distribution of objects in the environment and paraverbal language. 8 Communication is one of the competences provided for the training of nurses, being considered a fundamental instrument for care, especially in the interaction among health professionals, favoring the construction of inter-relationships among the team members and greater motivation for work.…”
Section: Introductionmentioning
confidence: 99%